Therapeutic engagement between consumers in suicidal crisis and mental health nurses. (27th February 2014) - Lees, David; Procter, Nicholas; Fassett, Denise
Abstract: Registered nurses within public mental health services play crucial roles in helping people recover from suicidal crisis. However, there is a lack of understanding of how care is experienced in this context, and available evidence suggests that nurses and consumers are often dissatisfied with the quality of care. There is thus an imperative to generate understanding of needs and experiences of both groups with a view to informing practice development. This article summarizes qualitative findings from a multimethod study undertaken in Australia, which surveyed and interviewed mental health nurses who had recent experience of caring for consumers in suicidal crisis in a hospital setting, and interviewed consumers who had recovered from a recent suicidal crisis. A framework was developed to guide the study and support ethical imperatives; in particular, the promotion of consumer well‐being. The findings highlight that therapeutic interpersonal engagement between nurses and consumers was central to quality care. This was particularly noted, as engagement could help reduce consumer isolation, loss of control, distress, and objectification of the delivery of potentially‐objectifying common interventions. Of concern, the results indicate a lack of therapeutic engagement from the perspective of both consumers and nurses. Recommendations to promote fuller therapeutic engagement are presented.